Polypropylene composite material as well as preparation method and application thereof
By combining copolymerized polypropylene with cationic and anionic polyacrylamide, combined with maleic anhydride grafted polypropylene, the problems of insufficient melt strength and appearance floating fibers of the polypropylene composite during blow molding are solved, and high Polypropylene composite material with strength and excellent appearance, suitable for the manufacturing of automotive pedals.
Patent Information
- Application Number
- CN202411541896.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing glass fiber reinforced polypropylene composites are insufficient in the melt strength during the blow molding process, prone to rupture, and cannot fully wrap the fiber, resulting in serious floating fiber appearance and cannot meet the mechanical strength and aesthetic requirements of the car pedals.
The combination of copolymerized polypropylene, cationic polyacrylamide, anionic polyacrylamide and maleic anhydride grafted polypropylene is adopted to increase the melt strength through the crosslinking point, and the fibers are fully wrapped through the screw extruder granulation process. .
It significantly improves the melt strength of polypropylene composite material, avoids cracking problems during blow molding, and improves the appearance quality of the product, meeting the mechanical strength and aesthetic requirements of the car pedals.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials and technology, and in particular relates to a polypropylene composition and a preparation method thereof. Background Art
[0002] Polypropylene is a thermoplastic material with the characteristics of low density, non-toxicity, environmental protection and recyclability. It can be widely used in many fields such as automobiles, home appliances and chemicals. In the automotive field, polypropylene resin is often used to replace metal materials in automobile pedals to speed up the pedal molding cycle, reduce production costs, and achieve lightweight, which meets the development requirements of the automotive industry.
[0003] Car pedals must be strong enough to withstand repeated trampling. The mechanical strength of ordinary polypropylene resin cannot meet the requirements. Glass fiber must be added to achieve the required mechanical strength. In order to further reduce the weight of car pedals and achieve further lightweight, automobile companies will gradually adopt blow molding technology to manufacture car pedals.
[0004] However, the melt strength of the polypropylene compound reinforced with glass fiber is insufficient and it is easy to break during the blow molding process. It is not suitable for three-dimensional blow molding and cannot meet the requirements of the three-dimensional blow molding process of automobile pedal materials. Secondly, the crystallization speed of the polypropylene compound is too fast to fully wrap the glass fiber in its system, resulting in serious floating fibers in the appearance of the final product, which reduces the aesthetics and commercial value of the product.
[0005] Chinese invention patent application CN115010920B discloses a high melt strength polypropylene and a preparation method thereof. High melt strength is a key factor in blow-molded foot pedals, but the application does not mention the appearance problem. If glass fiber is added to this type of polypropylene material, the pedals produced will have a serious risk of floating fibers in appearance.
[0006] Chinese invention patent application CN109679028B discloses a high melt strength polypropylene and a preparation method thereof and polypropylene foam beads and a preparation method thereof. The application mainly relates to the field of foaming materials. The strength cannot meet the requirements of blow-molded pedals and cannot be used in the production of automobile pedals. Summary of the invention
[0007] The purpose of the present invention is to solve the above technical problems and provide a polypropylene composite material with high melt strength to prevent breakage during blow molding and to fully wrap glass fibers during blow molding to ensure that the manufactured product has a good appearance.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned polypropylene composite material.
[0009] Another object of the present invention is to provide an application of the above-mentioned polypropylene composite material.
[0010] The present invention is achieved through the following technical solutions: A polypropylene composite material, comprising the following components in parts by weight: Polypropylene 59-81 parts; Glass fiber 10-30 parts; Polyacrylamide 3-10 parts; Maleic anhydride grafted polypropylene 1-10 parts; Antioxidant 0.1-2 parts; The polypropylene is selected from copolymerized polypropylene.
[0011] Preferably, the polypropylene melt flow rate is 0.1-10 g / 10 min, the test standard is in accordance with ISO 1133-2011, and the test conditions are a temperature of 230° C. and a load of 2.16 kg.
[0012] Preferably, the mass percentage of the polypropylene in the polypropylene composite material is not less than 59%.
[0013] Preferably, the average diameter of the glass fibers is 10-15 μm, and the average length is 3-5 mm.
[0014] Preferably, the weight ratio of polyacrylamide to maleic anhydride grafted polypropylene is in the range of (1-4):1.
[0015] Preferably, the polyacrylamide is selected from cationic polyacrylamide, anionic polyacrylamide, or a mixture of cationic polyacrylamide / anionic polyacrylamide.
[0016] Cationic polyacrylamide and a combination of cationic polyacrylamide / anionic polyacrylamide are preferred.
[0017] More preferred is a mixture of cationic polyacrylamide / anionic polyacrylamide.
[0018] Preferably, the weight average molecular weight of the cationic polyacrylamide is 4 million to 12 million, preferably 9 million to 11 million; the weight average molecular weight of the anionic polyacrylamide is 12 million to 20 million. The detection method is: high temperature GPC test, the specific steps include: Preparation of calibration standard substances: Select polymers with known molecular weight as calibration standard substances and prepare a set of standard substance solutions with different molecular weights.
[0019] Sample pretreatment: Dissolve the sample to be tested in an appropriate solvent and perform necessary pretreatment steps, such as filtering to remove impurities.
[0020] Instrument debugging: Debug various parameters of the GPC instrument, such as flow rate, temperature, etc., to ensure that the instrument operates in the best condition.
[0021] Sample injection: The calibration standard and the sample to be tested are injected into the column of the GPC instrument in sequence.
[0022] Column separation: In a GPC column, polymers in a solution are separated within the column according to their molecular weight.
[0023] Detection: At the outlet of the column, an appropriate detector is used to measure the response signal of the solution, such as refractive index, light scattering or viscosity.
[0024] Data processing: Based on the measurement results and response signals of the calibration standard substances, data processing is performed through calculation and analysis software to draw molecular weight distribution curves or calculate average molecular weight, etc.
[0025] Preferably, the weight ratio of cationic polyacrylamide to anionic polyacrylamide in the cationic polyacrylamide / anionic polyacrylamide compound is 1:(0.01-5); the preferred compounding weight ratio is 1:(0.5-1.5).
[0026] The inventors speculate that polyacrylamide can provide crosslinking points during the blow molding process, thereby improving the overall melt strength, and the larger the molecular weight, the more obvious the improvement. Anionic polyacrylamide also has a crosslinking effect, but the improvement is not as good as cationic polyacrylamide. The inventors found that when anionic and cationic types are mixed in a certain proportion, the melt strength is further improved and the appearance grade is also improved.
[0027] Preferably, the grafting rate of maleic anhydride grafted polypropylene is 0.6-1.1%, and the detection method is acid-base titration method.
[0028] Preferably, the antioxidant comprises a primary antioxidant and a secondary antioxidant, wherein the primary antioxidant is selected from hindered phenol antioxidants; and the secondary antioxidant is selected from phosphite antioxidants.
[0029] The primary antioxidant is selected from any one or more of 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate or 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; and the secondary antioxidant is selected from tris(2,4-di-tert-butylphenyl) phosphite.
[0030] Preferably, the primary antioxidant is selected from hindered phenol antioxidants containing isocyanuric acid groups.
[0031] More specifically, the primary antioxidant is selected from 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid.
[0032] The isocyanuric acid group is beneficial to improving the overall cross-linking degree, thereby further improving and improving the melt strength and floating fiber problem of polypropylene composite materials.
[0033] Those skilled in the art may choose to add 0.1-2 parts by weight of masterbatch according to actual needs.
[0034] The invention provides a method for preparing the polypropylene composite material, comprising the following steps: mixing the components uniformly according to the proportion, extruding and granulating the components through a screw extruder, wherein the screw temperature ranges from 180 to 210° C. and the screw speed ranges from 450 to 500 rpm.
[0035] The present invention also provides an application of the polypropylene composite material for preparing automotive functional parts.
[0036] In addition, the present invention provides a blow-molded product, wherein the blow-molded product comprises the above-mentioned polypropylene composite material.
[0037] The present invention has the following beneficial effects: The present invention provides cross-linking points for the compounding system by copolymerizing polypropylene with polyacrylamide, which can significantly improve the melt strength of the fiber-reinforced polypropylene composite material, and can also achieve the effect of fully wrapping the fibers during the blow molding process to avoid floating fibers in the appearance. The polypropylene composite material provided by the present invention solves the problem of easy rupture of the melt during the blow molding process, and can also ensure that the appearance of the produced product is excellent. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0039] The sources of raw materials used in the present invention are as follows: Polypropylene 1: PP T30S, homopolypropylene, with a melt mass flow rate of 3.0 g / 10 min at 230° C. and a load of 2.16 kg, purchased from Sinopec.
[0040] Polypropylene 2: PP B8101, copolymer polypropylene, with a melt mass flow rate of 0.5 g / 10 min at 230° C. and 2.16 kg load, purchased from Sinopec.
[0041] Polypropylene 3: PP 3010, copolymer polypropylene, with a melt mass flow rate of 1.1 g / 10 min at 230° C. and a load of 2.16 kg, purchased from the Plastic Industry Co., Ltd.
[0042] Maleic anhydride grafted polypropylene 1: BONDYRAM 1001CN, grafting rate 0.8%, purchased from Polyram.
[0043] Maleic anhydride grafted polypropylene 2: PA-BOND 363C, grafting rate 0.7%, purchased from Ploymer Asia.
[0044] Glass fiber: ECS13-4.5-T538D, monofilament diameter 13 μm, short cut length 4.5 mm, purchased from Taishan Glass Fiber Co., Ltd.
[0045] Polyacrylamide 1: C508, cationic, molecular weight 5 million, purchased from Mitsui Chemicals.
[0046] Polyacrylamide 2: C507, cationic, molecular weight 7 million, purchased from Mitsui Chemicals.
[0047] Polyacrylamide 3: C535, cationic, molecular weight 10 million, purchased from Mitsui Chemicals.
[0048] Polyacrylamide 4: A130, anionic, molecular weight 13 million, purchased from Mitsui Chemicals.
[0049] Polyacrylamide 5: A95, anionic, molecular weight 15 million, purchased from Mitsui Chemicals.
[0050] Polyacrylamide 6: A110, anionic, molecular weight 19 million, purchased from Mitsui Chemicals.
[0051] Masterbatch: PLASBLAK® PE2772KF, purchased from CABOT.
[0052] Primary antioxidant 1: SONOX 1010, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, hindered phenols, purchased from Shandong Linyi Sanfeng Chemical Co., Ltd. Primary antioxidant 2: AO-330, 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, hindered phenol, purchased from Aidico.
[0053] Primary antioxidant 3: SONOX 3114, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid, hindered phenols, purchased from Shandong Linyi Sanfeng Chemical Co., Ltd.
[0054] Secondary antioxidant: SONOX 168, tris(2,4-di-tert-butylphenyl) phosphite, phosphites, purchased from Shandong Linyi Sanfeng Chemical Co., Ltd.
[0055] The various testing methods of the present invention are as follows: (1) Appearance test: Injection mold a 100*100*3mm square plate and visually evaluate the appearance of floating fibers. Setting level: Level 0: No floating fibers; Level 1: Very slight; Level 2: Slightly visible; Level 3: Clearly visible; Level 4: Relatively serious; Level 5: Very serious.
[0056] (2) Melt strength test: The melt strength is measured by a Haake rheometer at a temperature of 190°C, in N.
[0057] Table 1 Weight parts of each component and test results of propylene composite materials of Examples 1-9 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Polypropylene 2 70 Polypropylene 3 60 80 75.6 75.6 75.6 75.6 75.6 75.6 Maleic anhydride grafted polypropylene 1 1 5 3 3 3 3 3 3 Maleic anhydride grafted polypropylene 2 10 Fiberglass 10 20 30 20 20 20 20 20 20 Polyacrylamide 1 3 6 Polyacrylamide 2 6 Polyacrylamide 3 7 6 Polyacrylamide 4 6 Polyacrylamide 5 6 Polyacrylamide 6 10 6 color masterbatch 1 1 1 1 1 1 1 1 1 Primary Antioxidant 1 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Primary Antioxidant 2 0.2 Primary Antioxidant 3 0.2 Secondary antioxidant 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Melt strength test / N 0.21 0.33 0.33 0.29 0.31 0.32 0.27 0.29 0.3 Appearance test 2 2 3 2 2 2 2 2 2 It can be seen from Examples 4-9 that the polypropylene composition to which cationic polyacrylamide is added has higher melt strength than the polypropylene composition to which anionic polyacrylamide is added, and the greater the molecular weight of the polyacrylamide, the higher the melt strength.
[0058] Table 2 Weight parts of each component of propylene composite material of Examples 10-14 and test results Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Polypropylene 3 75.6 75.6 75.6 75.6 75.6 Maleic anhydride grafted polypropylene 1 3 3 3 3 3 Fiberglass 20 20 20 20 20 Polyacrylamide 3 0.5 2 3 3 3 Polyacrylamide 6 5.5 4 3 3 3 color masterbatch 1 1 1 1 1 Primary Antioxidant 1 0.2 0.2 0.2 Primary Antioxidant 2 0.2 Primary Antioxidant 3 0.2 Secondary antioxidant 0.2 0.2 0.2 0.2 0.2 Melt strength test / N 0.32 0.34 0.36 0.36 0.45 Appearance test 1 1 1 1 0 It can be seen from Examples 10-12 that when the weight ratio of cationic polyacrylamide to anionic polyacrylamide is in the range of 1:(0.01-5), the performance is better, and when the weight ratio is 1:(0.5-1.5), the performance is even better.
[0059] Table 3 Weight parts of each component and test results of the propylene composite material of Comparative Examples 1-3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Polypropylene 1 75.6 Polypropylene 3 75.6 75.6 Maleic anhydride grafted polypropylene 1 3 3 Fiberglass 20 20 20 Polyacrylamide 3 3 3 Polyacrylamide 6 3 3 color masterbatch 1 1 1 Primary Antioxidant 1 0.2 Primary Antioxidant 3 0.2 0.2 Secondary antioxidant 0.2 0.2 0.2 Melt strength test / N 0.15 0.13 0.02 Appearance test 5 4 2 Comparative Example 1 is a conventional glass fiber reinforced polypropylene system, in which the resin matrix is selected from homopolymer polypropylene. During the blow molding process, the glass fiber cannot be fully wrapped due to the too fast crystallization speed, resulting in serious fiber floating in the product. In addition, the melt strength of the polypropylene composite material is also low.
[0060] Comparative Example 2 did not add maleic anhydride grafted polypropylene, and the melt strength and appearance tests were worse than those of the embodiment.
[0061] In Comparative Example 3, no polyacrylamide was added, and the melt strength was significantly reduced compared with that of the embodiment.
Claims
1. A polypropylene composite material, characterized in that: By weight, it includes the following components: Polypropylene 59-81 parts; Glass fiber 10-30 parts; Polyacrylamide 3-10 parts; Maleic anhydride grafted polypropylene 1-10 parts; Antioxidant 0.1-2 parts; The polypropylene is selected from copolymerized polypropylene.
2. The polypropylene composite material according to claim 1, wherein the weight ratio of the polyacrylamide to the maleic anhydride grafted polypropylene is in the range of (1-4):
1.
3. The polypropylene composite material according to claim 1, characterized in that: The polyacrylamide is selected from cationic polyacrylamide, anionic polyacrylamide, or a mixture of cationic polyacrylamide / anionic polyacrylamide; preferably cationic polyacrylamide, or a mixture of cationic polyacrylamide / anionic polyacrylamide; more preferably a mixture of cationic polyacrylamide / anionic polyacrylamide.
4. The polypropylene composite material according to claim 3, wherein the weight average molecular weight of the cationic polyacrylamide is 4 million to 12 million, preferably 9 million to 11 million.
5. The polypropylene composite material according to any one of claim 3, characterized in that: The weight ratio of cationic polyacrylamide to anionic polyacrylamide in the cationic polyacrylamide / anionic polyacrylamide compound is 1:(0.01-5); the preferred weight ratio is 1:(0.5-1.5).
6. The polypropylene composite material according to claim 1, characterized in that: The antioxidant includes a primary antioxidant and a secondary antioxidant, wherein the primary antioxidant is selected from hindered phenol antioxidants; and the secondary antioxidant is selected from phosphite antioxidants. Preferably, the primary antioxidant is selected from hindered phenol antioxidants containing isocyanuric acid groups.
7. The polypropylene composite material according to claim 1, characterized in that: According to the weight fraction, 0.1-2 parts of masterbatch are also included.
8. The method for preparing the polypropylene composite material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, and extruding and granulating the components through a screw extruder.
9. Use of the polypropylene composite material according to any one of claims 1 to 7, characterized in that: Used to prepare automotive functional parts.
10. A blow molded product, characterized in that: The polypropylene composite material comprises the polypropylene composite material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Long glass fiber reinforced composite polypropylene material, and preparation method and application thereof
CN103589103A
Polypropylene composite material
CN107418060A
Anti-static low-temperature durable polypropylene plastic
CN108822405A
Polypropylene composite material as well as preparation method and application thereof
CN113912949A
Antistatic long glass fiber reinforced polypropylene composite material and preparation method thereof
CN118359890A
